Peningkatan Aktivitas dan Hasil Belajar Melalui Picture And Picture Tematik IIID SDN 77 Kota Bengkulu - Tria, Rizki Tria Oktarina (JURIDIKDAS, 2024)
This study aims to increase the activity and student learning outcomes in thematic learning through the picture and picture learning model in class IIID SDN 77 Bengkulu City. This research is a Classroom Action Research (CAR). The subjects in this study were class IIID students at SDN 77 Bengkulu City for the 2023/2024 academic year. The number of students in class IIID, a total of 48 students with details of 29 male students and 19 female students. Data collection techniques using observation sheet techniques and test sheets. The data analysis technique used on the observation sheet, namely the average value formula and for learning outcomes uses the average value formula and the percentage of completeness of classical learning. The results showed that there was an increase in activity and student learning outcomes in Thematic learning. It was seen in cycle I that the average value of teacher activity was 26.5, increasing in cycle II with an average value of 34. In cycle I student activity the average value was 27.5 increased in the second cycle with an average value of 34. In the first cycle student learning outcomes of Indonesian language content with an average value of 70.31 with a percentage of 66.66% with a total of 32 students have a complete score. It increased in cycle II with an average score of 77.60 with a percentage of 85.41% with a total of 43 students having a complete score. In the SBdP cycle I learning content with an average score of 74.47 with a percentage of 79.16% with a total of 38 students having a complete score. It increased in cycle II with an average score of 80.20 with a percentage of 89.58% with a total of 43 students having a complete score. It can be concluded that through the picture and picture learning model can increase student learning activities and results in thematic learning class IIID SDN 77 Bengkulu City.